Diversity and Status of Butterflies in Mt. Timpoong and Mt. Hibok-hibok, Camiguin Island, Philippines - Toledo, Joliesa Mae Salmoy; Mohagan, Alma B. (JPAIR Multidisciplinary Research, 2011)
Diversity assessment of butterflies was conducted to provide information on species composition, diversity trends cross vegetation type's status, and distribution of butterflies in Mt. Timpoong and Mt. Hibok-hibok, Camiguin Island. This study was carried out using catching net to collect butterfly species in the two mountains of Camiguin namely Mt. Hibok-hibok and Mt. Timpoong from December 2009 to May 2010. The study revealed 81 species of butterflies in both mountains. 73 species were collected in Mt. Timpoong and 41 species in Mt. Hibok-hibok. Species richness of butterflies showed that there is a decreasing trend across vegetation types in both mountains. Highest diversity level was observed in the agro-ecosystem of Mt. Timpoong (H'= 1.70) and Mt. Hibok-hibok (H'=1.48) respectively. Status assessment showed 18 or 22 % endemic species out of which, 14 are present in Mt. Timpoong and only 8 are present in Mt. Hibok-hibok.
Keywords: butterflies; Mt. Hibok-hibok; Mt. Timpoong